Anti-inflammatory activity of collagen peptide in vitro and its effect on improving ulcerative colitis - Xuan-Ying Xin; Jing Zhou; Gao-Ge Liu; Mei-Yu Zhang; Xiang-Zi Li; Yan Wang (npj Science of Food)
Abstract To investigate the anti-inflammatory effects of collagen peptides, collagen peptides from cod skin were prepared to assess their in vitro anti-inflammatory effects and in vivo efficacy against ulcerative colitis. The results show that collagen peptides demonstrated anti-inflammatory effects by inhibiting the secretion of pro-inflammatory cytokines and reducing oxidative stress in vitro. In vivo, collagen peptides significantly reduced colonic tissue damage, modulated serum cytokine balance, increased the expression of tight junction proteins ZO-1, Occludin, and Claudin-1 in colon tissue, enhanced the abundance of beneficial bacteria while reducing harmful bacteria, and restored microbial balance. In addition, collagen peptides ameliorated colitis in vivo by inhibiting the phosphorylation of NF-κB p65, IκBα and p38 MAPK in the NF-κB/MAPK signaling pathway. Based on these findings, collagen peptides could serve as potential therapeutic agents for managing ulcerative colitis.